SISTEM INFORMASI PERUMAHAN ASTON VILLA BERBASIS WEB - Degita Astari Prakasiwi (JURNAL AKADEMIKA)
At this period, many people invest their assets in various things include a property such as a building or lot. Real estate developer is one of several companies who try make an advantage of this situation. The developer tries to reach as many consumer as possible. The developer intending to have a lot of promotion about the product. A possible promotion to do is online promotion. This research aims to design a website for Aston Villa Real Estate. Using a webhelps developer to promote their product efficien tly. And also, by using a web, the developer can promote their product anywhere and anytime. The consumer also get an advantage by using a website. Through this website, consumer can find any information about Aston Villa Real Estate faster and easier. This website provides any information about the products, types, specification, and also the price of the products.This website designed by using the programming language PHP, MySQL database, and for web server is using WAMP.